Pemberdayaan Krama Subak Sembung Peguyangan Dalam Rangka Pencegahan Alih Fungsi Lahan - I Gusti Bagus Suryawan; I Nyoman Sutama; I Gusti Agus Maha Putra Sanjaya (Postgraduated Community Service Journal, 2024)
The empowerment of Krama Subak Sembung Peguyangan in preventing conversion of agricultural land in Denpasar City is the main focus with the increase in land conversion by 50%, which threatens the sustainability of agriculture. The problem formulation includes the impact of land conversion and efforts to prevent it through legal counseling based on Regional Regulation No. 8 of 2021. Outreach to farmers through legal education has been carried out involving various stakeholders, including the Agriculture Service and legal practitioners. The Jamtani program was introduced to increase farmers' awareness and welfare, as well as reduce land conversion. Administrative constraints in electronic signature systems hinder the distribution of aid, which needs to be overcome with solutions such as the use of fingerprints or barcodes. The conclusion is that it is necessary to emphasize collaboration between government, academics and the community to maintain the sustainability of agricultural land, as well as strengthening the role of Subak as a traditional agricultural system that is integrated with local cultural values.